(untitled) (São Paulo Journal of Mathematical Sciences, 2007)
The author devised in [Math. USSR–Izv. 31 (1988) 481–501] a procedure that reduces the problem of classifying systems offorms and linear mappings to the problem of classifying systems oflinear mappings. We give a brief exposition of this method, reviewresults that were obtained by using this method (and were publishedmainly in Russian), and give examples of classification problems thatcan be solved by this method.